O Tribunal Penal Internacional Permanente no âmbito do sistema internacional: viabilidade e limites - Garcia Filho, Luiz da Rosa (2011)
This dissertation seeks to identify the role that the permanent International Criminal Court (ICC) occupies in the international system. In this paper, we analyze the formation of an international governmental organization (IGO) in light of theories of international relations, addressing the major theoretical schools, and giving special focus, to the applicability of the theory of hegemonic stability, bearing in mind the opposition that the United States offers to the Organization. We also draw a profile of the historical formation of the International Court, rescuing its predecessors and leaning on the principles that guide its activities, giving special attention to the principle of complementarity, which aims to safeguard the sovereignty of States Parties to the Rome Statute, an international treaty that gave start to ICC. Our research also takes care of the issue of the difficulties faced by this Court, in particular those under the opposition it faces in the International System (IS), addressing conciliation options and charting a prognosis for the future of the Organization in a world increasingly interdependent and globalized.